Correlation of proteolytic activity of Pseudomonas aeruginosa with site of isolation. - Janda, J M (1980)
Pseudomonas aeruginosa isolates were evaluated for protease activity by use of a semiquantitative plates assay. Differences were noted with respect to site of isolation, origin, and colonial morphology.